Impact of interpregnancy interval on the subsequent risk of adverse perinatal outcomes. Issue 11 (14th July 2015) - Ekin, Atalay; Gezer, Cenk; Taner, Cuneyt Eftal; Ozeren, Mehmet; Mat, Emre; Solmaz, Ulas
Abstract: Aim: The aim of this study was to investigate the impact of interpregnancy interval as a risk factor on multiple adverse perinatal outcomes. Material and Methods: Interpregnancy intervals and confounding factors were determined for healthy pregnancies (controls [ n  = 357]) and for pregnancies complicated by adverse perinatal outcomes. Interpregnancy interval was categorized as <6, 6–11, 12–17, 18–23, 24–35 and ≥36 months. Adverse outcomes included spontaneous labor leading to preterm birth ( n  = 265), preterm premature rupture of membranes ( n  = 245), pre‐eclampsia ( n  = 286), gestational diabetes ( n  = 302), abnormal placentation ( n  = 154), anemia ( n  = 314), congenital anomalies ( n  = 459), post‐partum hemorrhage ( n  = 326) and small for gestational age ( n  = 168). Multivariate logistic regression analysis was performed to assess the association of each outcome with the interpregnancy interval categories. Results: Spontaneous labor leading to preterm birth (odds ratio [OR], 1.86; 95% confidence interval [CI], 1.13–1.97), preterm premature rupture of membranes (OR, 1.69; 95%CI, 1.28–2.39), congenital anomalies (OR, 1.38; 95%CI, 1.09–1.76) and small for gestational age (OR, 1.68; 95%CI, 1.14–2.34) were significantly associated with intervals of <6 months. Among congenital anomalies, short interpregnancy interval represents an increased risk for cardiac defects (OR, 1.55; 95%CI, 1.09–5.46), neural tube defects (OR, 2.06; 95%CI, 1.32–7.64) and central nervous system anomalies (OR, 1.45; 95%CI, 1.12–3.65). Conclusion: Short interpregnancy interval is an independent risk factor for adverse perinatal outcomes.